A snake robot with mixed gaits capability - Khan, Md. Raisuddin; Ab Majid, Mad Helmi; Sidek, Shahrul Na'im (2012)
Snake robots are mostly designed based on single mode of locomotion. However, single mode gait most of the time fails to work effectively when they are required to work in different cluttered environment with different measures of complexity. As a solution, mixed mode locomotion is proposed in this paper by synchronizing serpentine gait for unconstricted workspace and wriggler gait for narrow space environment through development of a simple gait transition algorithm. This study includes the investigation on kinematics analysis followed by dynamics analysis while considering related structural constraints for both gaits. This approach utilized speed of the serpentine gait for open area operation and exploits narrow space access capability of the wriggler gait. Hence, this approach in such a way increases motion flexibility in view of the fact that the snake robot is capable of changing its mode of locomotion according to the working environment.